A Routing Scheme for IPv6-Based All-IP Wireless Sensor Networks. (27th November 2012) - Xiaonan, Wang; Shan, Zhong
Abstract : The paper proposes a routing scheme for IPv6-based all-IP wireless sensor networks. The paper creates the IPv6 address structure and the IPv6 address configuration algorithm for all-IP wireless sensor networks. Based on the IPv6 address structure, the paper proposes the routing algorithm in the link layer for all-IP wireless sensor networks. In the routing scheme, a sensor node stores the next channel-sampling time of its neighbor nodes. In this way, only during the next channel-sampling time, a sensor node keeps active. and during any other time it returns to sleep. Therefore, the routing performance is improved. and the power consumption is reduced. Finally, the paper discusses the reduced IPv6 protocol stack performing the routing scheme. The routing scheme's performance parameters are evaluated, including routing power consumption and delay, and the data results show the correctness and efficiency of the scheme.